Ethical and Legal Aspect of Assisted Reproductive Techniques - Oyebamiji, Oyesiji Rilwan; Landia, Natia (Caucasus Journal of Health Sciences and Public Health, 2016)
Infertility is the inability or failure to conceive or impregnate after at least one year of unprotected coitus and most of those who suffer from infertility live in developing countries. Its management is supposed to be an important component of reproductive health services. The rapid advancements in sciences have revolutionized modern medicine in a number of ways; genetic engineering, Assisted Reproductive Technologies (ART), human cloning, stem cells etc. has opened up the unimagined and promise unquestionable and undreamed benefits to mankind. At the same time, they raise many questions of law and ethical issues relating to public interest, social and religious sentiments and family concern. Although ethical judgments may indeed express personal preferences and may be connected in complicated ways with cultural conventions, ethics itself is a form of rational inquiry that concerns how we should live and what we should do. Some ethical issues are matters of debate. Background: Infertility is a prevalent condition in many developing countries with significant physical and psychosocial implications. The aim of this study is to discuss briefly about the ethics assisted reproductive technology (ART). Method: Articles were gathered from Google and other related journals for English language articles based on the topic at hand. Result: Ethical issues in the reviewed literature are based on developing countries and the main themes are surrogacy, sex selection and gamete donation. Conclusion: There should be stipulated guidelines to tackle the Ethical and legal issue of assisted reproductive technology.